Sulfur Induces Resistance against Canker Caused by Pseudomonas syringae pv. actinidae via Phenolic Components Increase and Morphological Structure Modification in the Kiwifruit Stems - Guifei Gu (MDPI AG, 2021)
Bacterial canker caused by Pseudomonas syringae pv. actinidiae (Psa) has led to considerable losses in all major kiwifruit-growing areas. There are no commercial products in the market to effectively control this disease. Therefore, the defense resistance of host plants is a prospective option. In our previous study, sulfur could improve the resistance of kiwifruit to Psa infection. However, the mechanisms of inducing resistance remain largely unclear. In this study, disease severity and protection efficiency were tested after applying sulfur, with different concentrations in the field. The results indicated that sulfur could reduce the disease index by 30.26 and 31.6 and recorded high protection efficiency of 76.67% and 77.00% after one and two years, respectively, when the concentration of induction treatments was 2.0 kg/m3. Ultrastructural changes in kiwifruit stems after induction were demonstrated by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and the activities of phenylalanine ammonia-lyase (PAL), peroxidase (POD) and polyphenol oxidase (PPO), and the accumulation of lignin were determined by biochemical analyses. Our results showed that the morphological characteristics of trichomes and lenticels of kiwifruit stem were in the best defensive state respectively when the sulfur concentration was 3.0 kg/m3 and 1.5 kg/m3. Meanwhile, in the range of 0.5 to 2.0 kg/m3, the sulfur could promote the chloroplast and mitochondria of kiwifruit stems infected with Psa to gradually return to health status, increasing the thickness of the cell wall. In addition, sulfur increased the activities of PAL, POD and PPO, and promoted the accumulation of lignin in kiwifruit stems. Moreover, the sulfur protection efficiency was positively correlated with PPO activity (p < 0.05) and lignin content (p < 0.01), which revealed that the synergistic effect of protective enzyme activity and the phenolic metabolism pathway was the physiological effect of sulfur-induced kiwifruit resistance to Psa. This evidence highlights the importance of lignin content in kiwifruit stems as a defense mechanism in sulfur-induced resistance. These results suggest that sulfur enhances kiwifruit canker resistance via an increase in phenolic components and morphology structure modification in the kiwifruit stems. Therefore, this study could provide insights into sulfur to control kiwifruit canker caused by Psa.